Do Stereotypical Media Representations Influence White Individuals' Perceptions of American Indians?. (July 2018) - Strass, Haley A.; Vogel, David L.
In this study, we examined exposure to stereotypical movie portrayals of American Indians, motivations to respond without prejudice, and awareness of White privilege on racist attitudes. European American participants ( N = 232) were randomly assigned to watch stereotypical representations of American Indians or control videos. Hierarchical regression results revealed that higher internal motivations to respond without prejudice and awareness were associated with lower levels of racist attitudes. Higher external motivations to respond without prejudice were associated with higher levels of modern racist attitudes. For participants high in awareness, there was no significant difference in modern racist attitudes between the control and stereotype conditions. For participants low in awareness, those in the control condition reported lower modern racist attitudes than those in the stereotype condition. Results suggest awareness is an important predictor of lower racist attitudes but needs to be reconceptualized within the counseling literature. Social justice implications and limitations are discussed.